Effect of structural factors on the physicochemical properties of functionalized polyanilines. Issue 13 (19th February 2020) - Andriianova, Anastasiia N.; Biglova, Yuliya N.; Mustafin, Akhat G.
Abstract : The review describes the relationship between the properties of functionalized polyanilines depending on the nature of the substituents at the aromatic ring. Abstract : This review discusses the physical and physicochemical properties of polyaniline (PANI) derivatives. The most important methods for the preparation of functionalized polyanilines are presented. The presence of various substituents in its structure changes the polymer characteristics significantly due to steric and electronic effects of the functional groups. This review describes the relationship between the properties of functionalized polyanilines depending on the nature, number and position of the substituents at the aromatic ring.